Effect of Pre-Heating and Post-Weld Local Heat Treatment on the Microstructure and Mechanical Properties of Low-Cost β-Titanium Alloy Welding Joints, Obtained by EBW - Belous, V.Yu; Selin, R.V.; Akhonin, S.V. (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2022)
Titanium (Ti) is highly valued for its strength-to-weight ratio and corrosion resistance. However, after it is processed to a wrought, or shaped form, it is typically in excess of 40 times more expensive than the corresponding steel part and nearly 20 times more expensive than the aluminum part. The high production costs of titanium in comparison to other structural metals is the main limiting factor for the wide employment of titanium. Cost reduction can be addressed considering creative fabrication methods and/or formulating new chemical compositions. In general, low-cost technology of titanium alloy can be implemented from raw material, alloy design and processing and forming. The core idea of low-cost titanium alloy design is to use cheap alloying elements to instead of expensive alloying elements without reducing the performance of the alloy. Iron has been considered for the development of few low-cost titanium alloys because of its stabilizing effect of the β-phase. Besides, it has a large solid solubility in β-Ti and owing to the atomic size difference with Ti can enable significant solution strengthening. But due to the high density of iron, high quantity of β-stabilizing elements and the formation of TiFe-based brittle intermetallic phases, welding joints of low-cost titanium alloys are prone to formation of cold cracks which is very important limiting factor for obtaining high quality welded joints with a strength of at least 90% compared to the strength of base material. Electron Beam Welding with its higher welding speed and intensity, can prevent formation of intermetallic and could help in obtaining welds with better mechanical properties, especially in combination with either pre-or post-welding heat treatment. The aim of this work is to study the effect of pre-heating and post-welding heat treatment on low-cost β-titanium alloy Ti-2.8Al-5.1Mo-4.9Fe welding joints by performing electron beam welding in combination with pre-and post-welding heat treatment. Specifically, this work will help to understand the influence of such techniques on the structure, phase composition and mechanical properties of low-cost β-titanium alloy welded joint.